Perbandingan Identifikasi Bangunan Sederhana Desa Kalirejo, Kecamatan Kokap, Kabupaten Kulon Progo Yogyakarta - SELY NOVITA SARI; triwuryanto; wahyu anisa dwi bekti (Retii, 2021)
The vulnerability of a building is a factor that can cause damage to the building or fail to achieve the expected performance in the event of a disaster. Efforts need to be made to reduce the risk of disasters, one of which is knowing the status of inhabited buildings by identifying their buildings. The method in this study is to compare the results of a simple building identification analysis using a simple building evaluation form (typical of walls) with the Building Rapid Assessment Application (ACeBS). The result of identifying whether it has similarities if done analysis with the same house but different methods. The results obtained from this study are as many as 46 houses (38%) of homes are in the same condition as the results using the ACEBS application. The status of the building from safe to vulnerable is 30 houses (25%). The condition of the building from safe to very vulnerable is 17 houses (14%). The status of buildings from unsafe to very vulnerable is 13 houses (11%). Cases of building change from unsafe to not vulnerable as many as 9 houses (7%,) and the case of building change from unsafe to vulnerable as many as 2 houses (2%). The condition of unsafe buildings becomes not vulnerable as many as 2 houses (3%).